REVERSE TRANSCRIPTION POLYMERASE CHAIN REACTION-A REVIEW - Sri, K. Bhavya; Banu, Shaheen; Sumakanth, Mogili (Journal of Global Pharma Technology, 2024)
The reverse transcription polymerase chain response is straightforward, powerful, and exquisite innovation in the discipline of molecular biology. It helps in determining the gene expression and amplifying the gene of interest in numerous fields used to locate and quantify the quantity of a given DNA collection. It entails three steps: reverse transcription, PCR amplification, and electrophoresis. Among PCR, the maximum commonly used PCR technique is reverse transcription polymerase chain reaction abbreviated as RT-PCR. it is way utilized in molecular biology & genetic research that allows the detection & quantification of mRNA. in this, RNA template is first converted into a complementary DNA by use of a reverse transcriptase enzyme and is further used for exponential amplification the use of the PCR method. Many genes are recognized to have their own promoter regions that inform cells where to begin transcribing the unique gene. RT-PCR first starts by using the usage of reverse transcriptase enzyme to make DNA out of RNA that has been extracted from cells or tissue samples. The RNA is in the shape of a polymer. The opposite transcriptase copies the RNA into an open-ended DNA strand, preventing it when it encounters a unique non-coding location known as a "poly-A tail" for each 20 to 23 nucleotides. The PCR method then begins by blending the newly made DNA with known primers to expand or reflect a selected piece of DNA. The pattern is then heated and cooled more than one instance, which causes the DNA to split into exclusive string sizes, brief and long. the quick string represents the newly copied RNA that can be visible as amplification, while the longer strand represents each the amplified RNA and all other non-amplified DNA portions collectively. The difference in the duration of DNA strands is what offers reverse transcriptase PCR its name. RT-PCR approach is performed in a thermocycler for the huge production of genetic fabric. It includes several wells, thermos regulators, a detector, and a gadget hooked up with appropriate software. Keywords: Amplification, Thermocycler, Gene expression, cDNA, Molecular biology, RT-PCR, Template.